Guías didácticas de Inglés Técnico, para el primer nivel de Ingeniería Mecánica, de la Universidad Técnica José Peralta de Azogues - Sayago A., Silvia
Students who had finished high school and registered at Jose Peralta University to get an academic degree in mechanical engineering have limited material at the beginning of Technical English level. For this reason, it is convenient to design a didactic material proposal under the conception of Didactic Guides in Technical English for students admitted in first level of English in mechanical engineering. It requires the planning of educational activities according to the student´sï necessity. The main idea is to get the students` integral personal, social and professional formation, to be able to communicate in oral or writing form in English, and understand every English material related with mechanical engineering.